Analisis Kinerja Keuangan Sebagai Dasar Investor Dalam Menanamkan Modal Pada PT. Bukit Asam,TBK (Study Kasus pada PT. Bukit Asam,TBK) - Farida Efriyanti; Retno Anggraini; Yunus Fiscal (Jurnal Akuntansi dan Keuangan, 2012)
Researchers conducted the study on PT. Bukit Asam Tbk, a company engaged in coal. In running the business of PT. Bukit Asam Tbk facing problems in measuring the achievements of the company based on the financial ratios of liquidity, solvency, activity and profitability. Over the last three years ie during the years 2009-2011. Rumussn problem is: "whether the financial performance affects investor in menananmkan mdal on PT.Bukit Acid, Tbk"? The purpose of this study the researchers did was to analyze the performance of keuanagn as the investor base to invest in PT.Bukit Acid, Tbk. Based on the analysis conducted by the authors, financial performance PT.Bukit Acid, Tbk terms of the ratio of liquidity, solvency, activity and profitability over the last three years increased. Suggestions submitted by the author is to maintain and improve the companys financial performance PT.Bukit Asam Tbk enable companies to more forward.